Inferior vena cava thrombosis in a case of amoebic liver abscess: Is hypercomplementemia responsible for this rare entity? - Sudha Chandelia; Sarika Jain; Dinesh Kumar Yadav; Nand Kishore Dubey (Wolters Kluwer Medknow Publications, 2014)
Among the liver abscesses, thrombosis of the inferior vena cava (IVC) has been reported mainly in amoebic liver abscess (ALA) caused by Entamoeba histolytica (E.H). It is an unusual complication especially in paediatric age group. Association of hypercomplementemia and IVC thrombosis has not been discussed previously. Published data suggest that E.H can activate the complement system and can cause hypercomplementemia. A very few studies suggest that complement activation and hypercomplementemia are associated with thrombus formation. We describe a paediatric case of ALA complicated by IVC thrombosis extending to the right atrium and discuss the possible role of hypercomplementemia in causation of IVC thrombosis in cases of ALA.